(untitled) (Medical Forum Monthly, 2021)
Objective: The basic aim of the study is to find the analysis of liver histology and severity of metabolic syndrome in patients suffering from nonalcoholic fatty liver disease. Study Design: Comparative study Place and Duration of Study: This study was conducted at the Allama Iqbal Memorial Teaching Hospital, Sialkot during October 2019 to May 2020. Materials and Methods: This is a comparison analysis in which we explored specific relationships between hepatic histology and markers of the metabolic syndrome. There were total 50 patients that included in this study. The diagnosis was based on the histological presence of macrovesicularsteatosis, with or without lobular inflammation, hepatocellular degeneration, or fibrosis. Results: In this study the data was collected from 50 patients with biopsy-proven NAFLD, a relationship between the severity of the metabolic syndrome and NAFLD was observed. While proportions of biopsy correlated with hepatic steatosis, hepatic inflammation and fibrosis were related with the presence and seriousness of the metabolic syndrome. This finding has clinical ramifications, since hepatic ultrasound and serum transaminases have restricted utility in foreseeing hepatic inflammation and fibrosis and there is current dependence on liver biopsies to affirm the analysis and show anticipation. Conclusion: It is concluded that NAFLD is associated with a high prevalence of obesity. There was a trend towards an association between NASH and metabolic syndrome, in addition, patients with NAFLD with MetS were more likely to have severe steatosis and portal inflammation on liver biopsy.